The Trajectory of Regulatory Reform in the UK in the Wake of the Financial Crisis - MacNeil, Iain (2015)
There has been much talk about regulatory reform around the world in the wake of the financial crisis but relatively little action. As a major international financial centre the UK is very much at the centre of the debate and has a particular interest in the ultimate outcome.The financial crisis has exposed the weaknesses of ‘light-touch’ regulation and ‘principles-based’ regulation, which characterised the UK system in the pre-crisis phase. Changes to the institutional structure of regulation recently announced by the new coalition government, combined with changes to regulatory style, are likely to have far reaching consequences for the practice and intensity of regulation in the UK. This article reviews and assesses recent and proposed regulatory changes and considers the relationship between corporate governance and regulation. It evaluates the impact on the UK system of initiatives undertaken at the international and EU levels as well as various interests and incentives